Antibacterial Activity of Red Ginger (Zingiber officinale) Extract Against Diarrhea Causing Bacteria Using the Well Diffusion Method - Fuzianingsih, Eka Noviya; Rahmawati, Ayu Sintya Citra; Safitri, Yunita Diyah (Jurnal Biologi Tropis, 2025)
Acute diarrhea resulting from bacterial infections remains a significant concern in public health. The improper or excessive use of antibiotics contributes to the emergence of antibiotic resistance, creating a need for safer therapeutic alternatives derived from natural sources, such as red ginger (Zingiber officinale). This study aimed to evaluate the antibacterial potential of red ginger extract against Escherichia coli, one of the common bacterial agents causing diarrheal disease. The assessment was carried out using the well-diffusion technique by observing and measuring the diameter of the inhibition zones produced by the extract. The extract was tested at concentrations of 40%, 60%, and 80%, accompanied by a positive control (ciprofloxacin 1 mg/mL) and a negative control (distilled water). The findings demonstrated that the positive control produced a mean inhibition zone of 44.375 mm, whereas the negative control showed no inhibitory activity. The 40% extract yielded an average inhibition zone of 17.125 mm, the 60% concentration produced 19.625 mm, and the 80% concentration generated an average diameter of 22 mm. Statistical evaluation using one-way ANOVA indicated a significance level of ≤ 0.05, and the Duncan post hoc analysis confirmed significant differences between all extract concentrations compared to the antibiotic control. Overall, the study demonstrated that red ginger extract possesses substantial antibacterial activity and effectively suppresses the growth of diarrhea-causing E. coli through the well-diffusion approach.